Um estudo sobre o papel das mídias sociais como instrumento de mediação para o ensino e a aprendizagem da língua brasileira de sinais (Libras) - Oliveira, Benelzo Batista (2023)
Considering the importance of the use of social media, such as YouTube, Facebook, Instagram, among others, in consolidating teaching and learning, this research aims to carry out an investigative study on the use of social media as platforms for teaching the Brazilian Sign Language (Libras). More specifically, it discusses how deaf and hearing people interested in learning sign language make use of the internet. It also approaches online education with a focus on the technologies used in teaching and learning Libras by deaf teachers, sign language interpreters and students. This work seeks to answer the following question: how can technologies help in the pedagogical practice of teaching Libras? To do so, it discusses the place that the deaf occupy on the internet, as well as addresses online education, focusing on the technologies used in the teaching of Libras, based on studies such as Dorziat and Figueiredo (2003), Santos and Pequeno (2011), Costa and Miota (2011) and Lopes (2017). The research methodology has a qualitative approach and uses bibliographic and exploratory deepening instruments. It is hoped that the results achieved can encourage the importance of further research on the use of technologies, especially social networks, in the education of the deaf.